Analytical study of foreign trade in the Iraqi economy for the period 2010 – 2020 - DUHAIM, DR. KAWTHER MOHAMMED (The journal of contemporary issues in business and government, 2022)
Iraq suffers from the chaos of economic openness to the outside world in terms of investment, financial and commercial investments, especially foreign trade. Therefore, we find that the liberalization of foreign trade after 2003 made the Iraqi economy dependent on the economy of other countries, and this led to an increase in economic exposure to the countries of the outside world and a decrease in the contribution of the agricultural, industrial and service sectors to the formation of the gross domestic product. One of the most important conclusions of the research is to work on reducing dependence The oil sector should finance Iraqi exports and work to benefit from oil revenues in increasing the production capacities of the various economic sectors.